A very low carbohydrate diet for minimising blood glucose excursions during ultra-endurance open-water swimming in type 1 diabetes: a case report - Smee, S. N.; Johnson, R.; Rush, A.; Davey, R. J. (Applied Physiology, Nutrition, and Metabolism, 2024)
Carbohydrate-restricted diets are used by people with type 1 diabetes (T1D) to help manage their condition. However, the impact of this strategy on blood glucose responses to exercise is unknown. This study describes the nutritional strategies of an athlete with T1D, who follows a very low carbohydrate diet to manage her condition during an ultra-endurance open-water swimming event. The athlete completed the 19.7 km distance in 6 h 43 min. She experienced minimal disruptions to glycaemia, reduced need for supplemental carbohydrate, and no episodes of symptomatic hypoglycaemia. This case report will hopefully encourage further experimental studies that inform and expand current clinical practice guidelines.